2000 Report on Grains Research and Educational Programs - Kansas State University, Agricultural Experiment Station and Cooperative Extension Service. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service., 2017)
We are pleased to provide this update on research and educational activities made possible with checkoff funds from the Kansas Corn, Grain Sorghum, Soybean, and Wheat Commissions. The Commissions provided $2,223,926 in support in fiscal year 1999 — Corn, $399,266; Grain Sorghum, $485,678; Soybean, $630,804; and Wheat, $708,178. These funds have been utilized by teams of research scientists and extension specialists to address issues that are important to our clientele. Agriculture is becoming more complex. Kansas producers depend on the Kansas Agricultural Experiment Station and Cooperative Extension Service to provide them with information that will improve their operations in order to maintain a competitive edge in an ever-changing global market. It is vital that K-State Research and Extension continues to serve Kansas producers and it is more important than ever that we supplement our limited state and federal funds with industry support. Funding from the Commodity Commissions is very much appreciated, both for the above reasons and because our association with them helps us to focus our efforts on issues important to producers. Findings reported in this publication span cropping systems, water management and quality, pest management, breeding for disease and pest resistance, genetic studies to improve quality and performance, alternative uses for end products, processing, and marketing. Because all projects have the common aim of answering real problems, Kansas producers will benefit directly. The results are already being communicated to various audiences through scientific journals, seminars, workshops, and field days, and they are being incorporated into K-State Research and Extension educational efforts.
Citation: Kansas State University, Agricultural Experiment Station and Cooperative Extension Service. (2001) 2000 Report on Grains Research and Educational Programs. Kansas State University. Agricultural Experiment Station and Cooperative Extension Service.